Peranan Dana Bantuan Keluarga Harapan (PKH) Dalam Meningkatkan Keseahteraan Ekonomi Umat Kajian Hukum Ekonomi Syari’ah - Munir, Ridwan; Anisah, Anisah (STAI Al Musaddadiyah Garut, 2023)
In Islam, social assistance is social assistance to help all people, and there is an encouragement to help each other for good because of the assistance provided both in the form of basic needs needed by the community, namely basic necessities, cash, and education and health services. So that. The problems examined in this study are: 1). How is the Role of Family Hope Program (PKH) assistance funds on improving the economic welfare of people in Haurpanggung Garut Village?, (2). Is the distribution of Family Hope Program (PKH) aid funds in Haurpanggung Village in accordance with Sharia Economic Law? The objectives of the study are: 1). To analyze what is the role of Family Hope Program (PKH) assistance funds on improving the economic welfare of people in Haurpanggung Garut Village?, (2). Is the distribution of Family Hope Program (PKH) aid funds in Haurpanggung Village in accordance with Sharia Economic Law? The research method used is